Uma leitura do simbologismo da casa na literatura de autoria feminina: Ondina Ferreira e Alina Paim - Silva, Marcio Carvalho da (2024)
This thesis is about the representation of the category of space in the works Casa de pedra (1952) and A correnteza (1979), written by the novelists Ondina Ferreira (1909- 2000) and Alina Paim (1919-2011), respectively. Focusing on the house as an entity - symbolic and dynamic - and a symbol - identity and memory - we analyze the transition from its pragmatic architectural function to its conversion into a vital element in the construction of the plot and in the characterization of the characters Leda and Isabel, the protagonists of Casa de pedra and A correnteza, in that order. The hypothesis is that in the novels by Ondina Ferreira and Alina Paim, space is not just a setting for narrative action, but a significant intersection between being and space. Throughout this research, we have sought to understand the nature of the symbiotic relationship between the protagonists and their homes. On the one hand, since the domestic space is the locus of the characters' experiences, the dynamic relationship between the physical place of the house and the intimacy of the characters is highlighted. On the other hand, since the house is the microcosm that mirrors and influences the protagonists' personalities, the correlation between the spatial organization of the rooms and the decorative objects inside the houses and their intertwining with the emotional disposition, conflicts and experiences of Leda and Isabel is shown. This argument is made possible by the interdisciplinary analytical proposal, which is linked to topoanalysis, with Gaston Bachelard (1988), Ozíris Borges Filho (2007) and Yu-Fu Tuan (2012). Among the texts consulted for this research, we highlight those that deal with literary criticism defended by Luis Alberto Brandão (2013), Osman Lins (1976), Antônio Dimas (1985) and Denílson Lopes (2007). On feminist literary criticism, we have Elódia Xavier (2012), Nelly Novaes Coelho (2002), Lucia Osana Zolin (2003), Ana Maria Leal Cardoso (2010) and Carlos Magno Santos Gomes (2014). And to better support the interdisciplinary approach, we consulted imaginary theorists such as Gilbert Durand (2012), Erich Neumann (2021), Mircea Eliade (1992), Jean Chevalier and Alain Cheerbrant (2015), among others. Our reading of the house is also reinforced by the anthropology of Gilberto Freyre (2003), Roberto DaMatta (1985) and Marc Augé (1994). When considering the novels of these writers, the house, as an entity and symbol, acts as a horizon in the creation of meanings and intersection between the characters and the space. To this end, Leda and Isabel, the domestic space and its constituents are an indication of the expansion of this element of the narrative and the insertion of an interdisciplinary analytical approach, traits on which the literature of female authorship and this thesis maintain attention.